Applying appropriate-use criteria to cardiac revascularisation in India. Issue 3 (30th March 2016) - Sood, Neeraj; Ugargol, Allen P; Barnes, Kayleigh; Mahajan, Anish
Abstract : Objectives: The high prevalence of coronary heart disease and dramatic growth of cardiac interventions in India motivate an evaluation of the appropriateness of coronary revascularisation procedures in India. Although, appropriate-use criteria (AUC) have been used to analyse the appropriateness of cardiovascular care in the USA, they are yet to be applied to care in India. In our study, we apply AUC to cardiac care in Karnataka, India, compare our results to international applications of AUC, and suggest ways to improve the appropriateness of care in India. Setting: Data were collected from the Vajpayee Arogyashree Scheme, a government-sponsored health insurance scheme in Karnataka, India. These data were collected as part of the preauthorisation process for cardiac procedures. Participants: The final data included a random sample of 600 patients from 28 hospitals in Karnataka, who obtained coronary artery bypass grafting or percutaneous coronary intervention between 1 October 2014 and 31 December 2014. Primary and secondary outcome measures: We obtained our primary baseline results using a random imputation simulation to fill in missing data. Our secondary outcome measure was a best case–worst case scenario where missing data were filled to give the lowest or highest number of appropriate cases. Results: Of the cases, 86.7% (CI 0.837% to 0.892%) were deemed appropriate, 3.65% (CI 0.023% to 0.055%) were inappropriate and 9.63% (CI 0.074% to 0.123%) were uncertain. Conclusions: The vast majority of cardiac revascularisation procedures performed on beneficiaries of a government-sponsored insurance programme in India were found to be appropriate. These results meet or exceed levels of appropriate use of cardiac care in the USA.